PENJADUALAN FLOWSHOP DENGAN ALGORITMA GENETIKA - Tessa Vanina Soetanto; Danny Prabowo Soetanto (Institute of Research and Community Outreach - Petra Christian University, 1999)
This paper explains and gives an application of genetic algorithm for flowshop scheduling at